Sports and energy drinks - Grumezescu, Alexandru Mihai; Holban, Alina Maria (Science of beverages, 2019)
Sports and Energy Drinks, Volume 10 in The Science of Beverages series, is the first single-volume resource to focus on the science behind these beverages-for-purpose products. As consumers seek ways to effectively replenish key nutrients after strenuous activity--while also balancing calories and vitamin intake--sports and energy drinks is one of the fastest growing markets in the industry. From protein to fruit, athlete to adolescent consumption, this book explores the key issues and challenges in developing products that meet consumer demand in a safe-and-effective manner. This series takes a multidisciplinary approach to help research and development professionals understand the scientific complexities of these unique beverages. As demand for sports and energy drinks is growing and with a more competitive market, this timely and useful resource will equip industry professionals with the tools they need to create new and innovative health-promoting products. Presents new findings on the health effects of sports and energy drinksProvides research analysis of existing products to promote new product innovationIncludes information on trace minerals to promote safety and quality